“Bekerja adalah waktu me time”: Eksplorasi persepsi me time pada ibu bekerja - Alverina, Yohana; Hanami, Yuliana; Abidin, Fitri Ariyanti (Jurnal Psikologi Ulayat, 2024)
Me time holds significance for personal enjoyment and relaxation, yet its exploration, particularly among Indonesian mothers, is limited. This qualitative study interviewed three full-time working mothers (aged 28, 30 and 36) to understand their perceptions in me time allocation before marriage, after marriage, and after having children. Thematic analysis identified six major themes: a) the importance of me time, b) factors hindering it, c) diverse interpretations, d) activities pursued, e) repercussions of inadequate me time, and f) coping strategies employed. This study underscores the significance of dedicating me time as a means to alleviate the stress experienced in day-to-day life. Maternal individuals exhibit an adaptive inclination to tailor their approach to personal time management in light of the demands imposed by motherhood. This research effectively accentuates the necessity of prioritizing me time to enhance holistic well-being and fortitude when confronted with maternal responsibilities.